2021
DOI: 10.1038/s41598-021-81523-x
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of commercially available aroA delated gene E. coli O78 vaccine in commercial broiler chickens under Middle East simulating field conditions

Abstract: The broiler industry in the Middle East (ME) faces many challenges related to bacterial infections, including M. gallisepticum, M. synoviae, E. coli, and other gram-negative bacteria, exacerbated by various errors in the brooding process. Antibiotics use in the first three days of life, such as Linco-Spectin 100 SP, tilmicosin, enrofloxacin, tylosin, colistin, and doxycycline, is the trend in the market to control such challenges. This study aimed to evaluate the efficacy of the newly introduced aroA E. coli v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The findings regarding heterologous protection were not consistent among studies with some showing effectiveness against certain strains [54,60], but not others [56,57,60]. The efficacy of the vaccine against homologous challenge was enhanced by supplementation of probiotics Enterococcus faecalis [58] and pre-treatment with Lincospectin improved the vaccine's response [61]. However, the immune response elicited by the live attenuated vaccine was reported to be interfered by the prior application of ceftiofur sodium antibiotic in layer PLOS ONE The crp deletion mutant vaccine was efficacious to reduce mortality and bacterial colonization after homologous challenge but was not effective against heterologous challenge (O125).…”
Section: Live and Live Attenuated Vaccinesmentioning
confidence: 78%
“…The findings regarding heterologous protection were not consistent among studies with some showing effectiveness against certain strains [54,60], but not others [56,57,60]. The efficacy of the vaccine against homologous challenge was enhanced by supplementation of probiotics Enterococcus faecalis [58] and pre-treatment with Lincospectin improved the vaccine's response [61]. However, the immune response elicited by the live attenuated vaccine was reported to be interfered by the prior application of ceftiofur sodium antibiotic in layer PLOS ONE The crp deletion mutant vaccine was efficacious to reduce mortality and bacterial colonization after homologous challenge but was not effective against heterologous challenge (O125).…”
Section: Live and Live Attenuated Vaccinesmentioning
confidence: 78%
“…Lozica et al [ 81 ] reported that an autonomous E. coli vaccine significantly reduced morbidity and mortality and increased egg production in poultry. Several studies showed that an E. coli vaccine, Poulvac® (Zoetis, Parsippany, NJ, USA) effectively worked against the avian pathogenic E. coli in poultry [ 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: A Review Of Current Research Studies On the Efficacy Of Bact...mentioning
confidence: 99%
“…Infections) 26 , 27 . Furthermore, it has also been reported that an E. coli O78 vaccine attenuated by deletion of the aro A gene was efficacious against avian diseases 28 . One of the main reason aroA is a good mutated background for vaccine strains is that it makes strains auxotrophic for aromatic amino acids and so cannot replicate properly in certain niches in the host 26 , 29 , 30 .…”
Section: Introductionmentioning
confidence: 97%